Temporoparietal Junction Hypoactivity during Pain-Related Empathy Processing in Adolescents with Conduct Disorder - Dong, Daifeng; Ming, Qingsen; Wang, Xiang; Yu, Weixia; Jiang, Yali; Wu, Qiong; Gao, Yidian; Yao, Shuqiao (Frontiers in Psychology, 2017)
Background. Lack of empathy has been proposed to account for the characteristic behavioral problems exhibited by adolescents with conduct disorder (CD). Hence, the aim of this study was to determine whether adolescents with CD exhibit atypical affective and cognitive neural empathic responses during pain-related empathy processing. Methods. A total of 30 adolescents with a CD diagnosis and 36 without CD symptoms were recruited from out-patient clinics and local middle schools in the same region, respectively. All 66 participants were subjected to functional magnetic resonance imaging (fMRI) while viewing video clips depicting a face with a neutral expression receiving non-painful stimulation (Q-tip touch) or a face with a painful expression receiving painful stimulation (needle penetration) applied to the left or right cheek. Results. The regions associated with affective and cognitive empathy were activated in the HC group during pain-related empathy processing. Compared to HCs, adolescents with CD showed significantly reduced activation in the bilateral temporoparietal junction (TPJ). Conclusions. Adolescents with CD exhibited dampened hemodynamic responses during pain-related empathy processing in the bilateral TPJ, a region associated with cognitive empathy. These findings are consistent with the hypothesis that adolescents with CD may have a cognitive empathy deficiency. Key words: Conduct disorder, empathy, fMRI, temporoparietal junction, adolescents.